Wordwall Media with a Gameshow-Quiz Type to Increase Students' Interest in IPAS Learning at Elementary School - Dewi, Sinta Maria; Nur DS, Yulistina; Sa’diah, Tia Latifatu; Sa’adah, Hilda Meida Rohimatu; Harmawati (Universitas Pendidikan Ganesha, 2024)
Student behavior and attitudes during learning, namely still seen as passive, easily bored, less involved, and often ignore teacher explanations when receiving lesson materials. This is caused by materials that only utilize monotonous learning media, are less innovative, and only rely on reading books for learning. The latest learning media are needed in learning. This study aims to develop Wordwall media with a Gameshow-Quiz type to enhance the learning interest of fourth-grade students in elementary school, specifically focusing on the subject of IPAS. This study employs the Dick and Carey model of research and development methodology. The sample in this research was a purposive sampling from fourth-grade classes. Data collection in this study involves the use of student interest questionnaires focused on the IPAS subject. Based on the research findings, it can be concluded that the development of learning media to enhance students' interest in IPAS achieves an average final score of 90%, indicating a mastery level among students. The feasibility of the learning media, evaluated by content experts and media specialists, confirms its validity and suitability for educational use.